Executive Bonus Contract Characteristics and Share Repurchases - Kim, Sunyoung; Ng, Jeff (The Accounting Review, 2018)
ABSTRACT We examine the importance of bonus contract characteristics, specifically, with respect to the relation between EPS-based bonuses and share repurchases. We find that managers are more (less) likely to repurchase shares and spend more (less) on repurchases when as-if EPS just misses (exceeds) the bonus threshold (maximum) EPS level. We find no such relation when as-if EPS is further below the threshold. We find weak evidence that managers of firms with as-if EPS just below the EPS target are more likely to repurchase shares and spend more on repurchases relative to firms with as-if EPS just above the EPS target. We further find that the incentive-zone slopes specified in the bonus contracts are positively associated with share repurchases. Managers making bonus-motivated repurchases do so at a higher cost. Together, our results highlight the importance of compensation design in motivating managers' behavior and aligning managers' incentives with shareholders. JEL Classifications: M41; M52.